Supplying Liquid Organic Fertilizer (POC) With Organic Waste Materials On The Growth And Product of Lettuce (Lactuca Sativa L.) - Bambang Gunawan; Nurul Huda; Andri Mulyono (Faculty of Agriculture, Merdeka University Surabaya, 2021)
Liquid organic fertilizers can come from feces (animals, humans), agricultural waste, agricultural processing waste, household waste, urban waste, and production waste. Waste in general is a case of environmental pollution which can cause environmental problems and deteriorate health for the community, this is caused by liquid waste obtained from various industrial activities, hospitals, markets, households, especially in food industry waste, because in the process it still leaves elements that can become part of the process water and discharged into the environment. The use of various wastes to become organic fertilizers is an effort to overcome the problem of environmental pollution, with high organic matter, waste can act as an organic source of food by microbial growth. The purpose of this study was to determine the various POC materials from organic waste that would have a better effect on growth and yield in lettuce plants. Based on the results of the study, it can be concluded as follows:There is a significant effect on plant length variables on wet weight per plant with R Square of 0.69884 (69.88%) at 28 days of age observation and number of leaves with R Square of 0 , 7025 (70.25%) at 35 days after transplanting and there was a significant effect of the K3 treatment (POC 12%), plant length and number of leaves on the wet weight per plant which gave a higher value than the K1 and K2 treatments with Adjusted R Square of 0.935293 (93.53%); but statistically not significant difference with treatment K2 (POC 8%) with Adjusted R Square of 0.706472 (70.65%).